Design and manufacture of metal membrane microperforated panel absorbers. (February 2019) - Nie, L; Li, S Q; Jia, W
Abstract: Metal Membrane MPP (Microperforated Panel) is a kind of promising acoustic absorber due to its steady absorption performance and the convenience in process. In order to reveal the effects of pivotal parameters on absorption coefficient, an acoustic model of MPP is derived based on classic theory. The optimized parameters are found using genetic algorithm by the aid of this model. The MPP samples made of aluminum are manufactured by laser drilling and then the absorption coefficient is measured in impedance tube. The result shows that the theoretical model can predicted the absorption behavior of metal MPP relatively accurately. And the peak absorption coefficient, peak frequency, and the half-absorption band width are about 0.9, 2000Hz and 3200Hz respectively.